Development of Booklet on Medicinal Plant Diversity As A Learning Medium - Fatikhatun Nikmatus Sholihah; Anggun Wulandari; Niken Koeswara Putri (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Learning in the classroom with less varied media causes students to tend to be bored in the learning process in the classroom. Students have never heard of the term booklet and have never used booklet learning media on medicinal plant biodiversity. This study aims to describe the results of the validation of booklet learning media material experts and the results of media expert validation of the use of booklet learning media on the diversity of medicinal plants in Peluk Hamlet as a learning medium. The type of research used is the type of development (Research and Development) with the ADDIE (Analayze, Design, Development, Implementation, Evaluation) model. This research is limited to the Development stage. The data collection instrument in this development research is in the form of a validation questionnaire. The validation of the booklet media instrument was carried out by two validators, namely material expert validators and media expert validators. The data analysis technique used is data obtained by researchers from expert validators and then analyzed qualitatively and quantitatively. The results of the study showed that the validation value by material experts was 91.25% declared very valid and the validation results of media experts were 92.5% declared very valid.